Differential responses of abomasal transcriptome to Haemonchus contortus infection between Haemonchus-selected and Trichostrongylus-selected merino sheep. (April 2022) - Liu, Jing; Zhou, Jiachang; Zhao, Si; Xu, Xiangdong; Li, Cong-jun; Li, Li; Shen, Tingbo; Hunt, Peter W.; Zhang, Runfeng
Abstract: Haemonchus contortus is the most prevalent and pathogenic gastrointestinal nematode infecting sheep and goats. The two CSIRO sheep resource flocks, the Haemonchus -selected flock (HSF) and Trichostrongylus -selected flock (TSF) were developed for research on host resistance or susceptibility to gastrointestinal nematode infection. A recent study focused on the gene expression differences between resistant and susceptible sheep within each flock, with lymphatic and gastrointestinal tissues. To identify features in the host transcriptome and understand the molecular differences underlying host resistance to H. contortus between flocks with different selective breeding and genetic backgrounds, we compared the abomasal transcriptomic responses of the resistant or susceptible animals between HSF and TSF flocks. A total of 11 and 903 differentially expressed genes were identified in the innate infection treatment in HSF and TSF flocks between resistant and susceptible sheep respectively, while 52 and 485 genes were identified to be differentially expressed in the acquired infection treatment, respectively. Among them, 294 genes had significantly different gene expression levels between HSF and TSF flock animals within the susceptible sheep by both the innate and acquired infections. Moreover, similar expression patterns of the 294 genes were observed, with 273 genes more highly expressed in HSF and 21 more highly expressed in the TSF within the abomasal transcriptome of the susceptible animals. Gene ontology enrichment of the differentially expressed genes identified in this study predicted the likely differing function between the two flock's susceptible lines in response to H. contortus infection. Nineteen pathways were significantly enriched in both the innate and adaptive immune responses in susceptible animals, which indicated that these pathways likely contribute to the host resistance development to H. contortus infection in susceptible sheep. Biological networks built for the set of genes differentially abundant in susceptible animals identified hub genes of PRKG1, PRKACB, PRKACA, and ITGB1 for the innate immune response, and CALM2, MYL1, COL1A1, ITGB1 and ITGB3 for the adaptive immune response, respectively. Our results offered a quantitative snapshot of host transcriptomic changes induced by H. contortus infection between flocks with different selective breeding and genetic backgrounds and provided novel insights into molecular mechanisms of host resistance.